Fuzzy Mathematical Morphology Toolbox and Graphical Interface - Bouchet, Agustina (2013)
The task of solving problems using Digital Image Processing requires of the choice of the correct methodology for the issues to be tackled, and a sound selection of parameters for each algorithm to be used. Fuzzy Mathematical Morphology is one of the existing techniques for image processing, being already applied with success on several problems of medical images analysis. However, the selection and use of its operators requires of the continual observation of the results, over a varied range of parameters, for the selection of the optimal ones. Toward that goal, in this work we develop a library of Fuzzy Mathematical Morphology operators, plus a flexible graphical interface, which is of great help in the selection of the optimal parameters and the implementation of Fuzzy operators, with the addition of several classical Image Processing operators. We describe the properties of the library and analyze the simplicity of the graphical interface.